Transformational leadership style as predictor of a decision making styles: Moderatig role of emotional intelligence - Rana Rashid Rehman; Ajmal Waheed (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
The current study examines the relationship among transformational leadership style and decision making styles. It also determines the moderating role of emotional intelligence in predicting this relationship. Three hypotheses are generated for the study i.e., two hypotheses are to measure the relationship among transformational leadership style and decision making styles whereas third hypothesis is to assess the moderating effect of emotional intelligence. Questionnaire method is used to collect data from 113 respondents. Regression analysis is utilized to study the relationship among transformational leadership style and decision making styles and step-wise regression analysis is used to study moderating effect of emotional intelligence. The study found that transformational leadership style strongly predicts rational and dependant decision making styles and weakly predict intuitive and spontaneous decision making styles while no association founds with avoidant decision making styles. Present research also found that emotional intelligence moderates the relationship among transformational leadership style and decision making styles.
Keywords: 330; Transformational leadership style; Decision making styles; Emotional intelligence